2001
DOI: 10.1007/s11892-001-0014-x
|View full text |Cite
|
Sign up to set email alerts
|

Birth weight as a predictor of type 2 diabetes mellitus: The U-shaped curve

Abstract: Recent findings have sparked intense interest in birth weight as a predictor of type 2 diabetes mellitus. In some populations, there is an inverse association between birth size and disease; however, in the Pima Indians, a population with very high rates of gestational diabetes, high birth weight and low birth weight are associated with diabetes. This results in a U-shaped curve with higher diabetes rates in both tails of the distribution. Similarly, there are reports of an inverse association between stature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
56
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(58 citation statements)
references
References 28 publications
1
56
1
Order By: Relevance
“…Most studies dealing with children or nonpregnant adults have reported an inverse linear relationship between birth size and the prevalence of disease (1-4,6 -10), but the relationship among the Pima Indians from Arizona has been described as "U-shaped" because the high risk is seen in individuals with high birth weight as well as low birth weight (5). Several reasons for this relationship have been proposed (13) and a similar finding was subsequently reported among schoolchildren in Taiwan (11). Since the 4th International Workshop-Conference on Gestational Diabetes Mellitus, where the association between a woman's birth weight and gestational diabetes mellitus (GDM) or pregestational diabetes was first presented (14), there have been several similar reports in the literature.…”
mentioning
confidence: 63%
“…Most studies dealing with children or nonpregnant adults have reported an inverse linear relationship between birth size and the prevalence of disease (1-4,6 -10), but the relationship among the Pima Indians from Arizona has been described as "U-shaped" because the high risk is seen in individuals with high birth weight as well as low birth weight (5). Several reasons for this relationship have been proposed (13) and a similar finding was subsequently reported among schoolchildren in Taiwan (11). Since the 4th International Workshop-Conference on Gestational Diabetes Mellitus, where the association between a woman's birth weight and gestational diabetes mellitus (GDM) or pregestational diabetes was first presented (14), there have been several similar reports in the literature.…”
mentioning
confidence: 63%
“…[32][33][34][35] In a recent birth cohort study of 2135 men and 2380 women who were born at Helsinki University Central Hospital between 1934 and 1944, who attended child welfare clinics and were still resident in Finland in the year 2000, Eriksson et al found that the incidence of obesity (based on lifetime maximum BMI ascertained from a postal questionnaire and defined as a BMIX30 kg/m 2 ) rose linearly with increasing body size at birth. 32 This study also found that the mean weight and BMI of people who later became obese exceeded the average and remained above average at a statistically significant level at all ages from 6 months to 12 years.…”
Section: Discussionmentioning
confidence: 99%
“…36,37 The slow growth-and accelerated growth-related adverse health outcomes in later life may represent different disease mechanisms, and both may be modified by growth during infancy and childhood. 32,35,38 Therefore, the significance of macrosomia is not just for its relationship with short-term outcomes such as prolonged labor, cesarean section, and birth injury. The possibility of increased risk on long-term health outcomes, such as obesity, in childhood and adulthood of macrosomia should be considered as well.…”
Section: Discussionmentioning
confidence: 99%
“…In some populations, there is an inverse association between birth size and disease. However, epidemiological studies confirm that the relationships between human birth weight and adult obesity, hypertension, and insulin resistance follow U-shaped curves [28][29][30]. An analysis of all of these reports suggests that the relationship between birth weight and these metabolic abnormalities in adult life can be described by a U-shaped curve.…”
Section: Discussionmentioning
confidence: 99%